THE EFFECT OF FOLIAR FERTILIZERS AND FUNGICIDES ON RED GINGER PRODUCTIVITY AND FARMING IN OVERCOMING PHYLLOSTICTA DISEASE - fitria naimatu sadiyah; Annisa Khoiriyah; Heriyanto (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
Phyllosticta zingiberi leaf spot disease causes leaf damage, causing low yields. Control efforts carried out by farmers have yet to yield maximum results, so effective and applicable control techniques are needed, including combining the use of fungicides and foliar fertilizers. The study aimed to determine the effective concentrations of fungicides and foliar fertilizers for controlling leaf spot disease and their effect on Red Ginger productivity and farming. The research was conducted in Argodadi Village, Sedayu District, Bantul Regency, from November 18, 2020, to August 18 2021, in a factorial manner which was arranged in a complete randomized block design consisting of 2 factors with three concentration levels, namely fungicide as much as 0 L/Ha, 6 L/Ha, 12 L /Ha and 0 L/Ha, 10 L/Ha, 20 L/Ha foliar fertilizer. The results showed that applying 6 L/Ha fungicides reduced the intensity of attacks and the percentage of plants affected by leaf spot disease by 56.03% and 65.90%, respectively. While the combination treatment of 12 L/Ha of fungicide and 20 L/Ha of foliar fertilizer was able to increase ginger productivity by increasing plant height, number of tillers, fresh ginger rhizome weight of 0.34 kg/plant and financial benefits in the farming of Rp. 49,180,916 per Ha with an R/C ratio of 1.35.